Effect of propagation method and site on stem attributes on 17 years-old Pinus radiata trees - Antillanca, Marcial; Trincado, Guillermo; Lasserre, Jean Pierre (Instituto de Ecología, A.C., 2017)
The rate of establishment of radiata pine plantations in Chile has required increasing the production of plants propagated by vegetative methods. However, it is unknown whether there are differences in growth rates and stem attributes between trees propagated by seedlings or cuttings. This study quantifies differences between plant reproduction methods (seedling and cutting) and its interaction with site on stem attributes of radiata pine trees at the age of 17 years old. The evaluated attributes were stem form, location of center of volume and center of gravity and taper of bottom logs. The required information was obtained from an un-thinned and un-prunned trial located in two contrasting site conditions on volcanic ash and sandy soils. On each site, two rectangular plots (30 m × 21 m) with initial stand density of 1428 individuals per hectare that belong to the same genetic family were established. For each plot, plants propagated by seedlings or one-year-old cuttings were randomly assigned. The combination of propagation methods and sites defined a 2 × 2 factorial experiment. From each treatment, twenty trees were selected for destructive sampling. The results obtained indicate that there are no significant differences between propagation methods for stem form, form quotient, location of the center of volume and center of gravity. There were also non-significant differences between sites and there was no interaction between sites and propagation methods. However, the taper of the first log (0 m - 3 m) was significantly different between propagation methods and between sites. We concluded that trees propagated by cuttings and established in a low productivity site on sandy soils have a more cylindrical first-bottom log in comparison to trees propagated by seedlings and established in a high productivity site on volcanic ash soils located in the Andean piedmont.